Connectivity of bacterial assemblages along the Loa River in the Atacama Desert, Chile (2018)
The Loa River is the only perennial artery that crosses the Atacama Desert in northern Chile. It plays an important role in the ecological and economic development of the most water-stressed region, revealing the impact of the mining industry, which exacerbate regional water shortages for many organisms and ecological processes. Despite this, the river system has remained understudied. To our knowledge, this study provides the first effort to attempt to compare the microbial communities at spatial scale along the Loa River, as well as investigate the physicochemical factors that could modulate this important biological component that still remains largely unexplored. The analysis of the spatial bacterial distribution and their interconnections in the water column and sediment samples from eight sites located in three sections along the river catchment (upper, middle and lower) was conducted using 16S rRNA gene-based Illumina MiSeq sequencing. Among a total of 543 ASVs identified at the family level, over 40.5% were cosmopolitan in the river and distributed within a preference pattern by the sediment substrate with 162 unique ASVs, while only 87 were specific to the column water. Bacterial diversity gradually decreased from the headwaters, where the upper section had the largest number of unique families. Distinct groupings of bacterial communities often associated with anthropogenic disturbance, including Burkholderiaceae and Flavobacteriaceae families were predominant in the less-impacted upstream section. Members of the Arcobacteraceae and Marinomonadaceae were prominent in the agriculturally and mining-impacted middle sector while Rhodobacteraceae and Coxiellaceae were most abundant families in downstream sites. Such shifts in the community structure were also related to the influence of salinity, chlorophyll, dissolvedoxygen and redox potential. Network analyses corroborated the strong connectivity and modular structure of bacterial communities across this desert river, shedding light on taxonomic relatedness of co-occurring species and highlighting the need for planning the integral conservation of this basin.